HARMONY BETWEEN NATURE AND CULTURE - Lobar Mukhtarova (Scholar Express Journal, 2024)
The article discusses the basic concepts of environmental education, the importance of environmental protection, reveals modern methods of developing environmental consciousness, including environmental education, education, culture and also educational activities
Keywords: environmental education and upbringing; culture; culturenatural sciences